2013
DOI: 10.1177/0192623313512429
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Parotid Gland Hypertrophy Induced by Dietary Treatment of GSE in Rats

Abstract: In a 13-week feeding toxicity study of grape skin extract (GSE) performed previously, 5.0% GSE showed diffuse hypertrophy and basophilia in rat parotid glands. To clarify whether the change in the parotid glands was an adverse effect of GSE, 6-week-old male F344 rats were fed a diet containing 5.0% GSE or were administered a dose corresponding to the dietary concentration via gavage for 4 weeks, and the treatment was stopped for 2 weeks. To ascertain the effect of astringency, other animals were fed a diet con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Importantly, the morphometric characteristics described above classify the observed parotidomegaly as “hypertrophia” rather than “hyperplasia,” which is defined as an increase in cell number, which was not observed in our study nor previous studies [ 41 ]. A similar reaction within acini was also observed in other studies on pigs [ 42 ] and rats [ 43 ]. Comparable to our results, these studies reported the enlargement of serous acini after feeding tannins to the animals and linked this enlargement to the higher secretory activity of acinar cells and the production of salivary proteins [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, the morphometric characteristics described above classify the observed parotidomegaly as “hypertrophia” rather than “hyperplasia,” which is defined as an increase in cell number, which was not observed in our study nor previous studies [ 41 ]. A similar reaction within acini was also observed in other studies on pigs [ 42 ] and rats [ 43 ]. Comparable to our results, these studies reported the enlargement of serous acini after feeding tannins to the animals and linked this enlargement to the higher secretory activity of acinar cells and the production of salivary proteins [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…A similar reaction within acini was also observed in other studies on pigs [ 42 ] and rats [ 43 ]. Comparable to our results, these studies reported the enlargement of serous acini after feeding tannins to the animals and linked this enlargement to the higher secretory activity of acinar cells and the production of salivary proteins [ 42 , 43 ]. Enlargement of salivary gland acini seems to be a common response to external stimuli promoting higher production of saliva or salivary proteins, as shown in the case of Leishmania infantum infection in dogs [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…It has also been reported that dietary supplementation with grape skin extract in rats (F344/ DuCrj) promotes an increase in the size of the gland and at cellular level the synthesis of larger secretory granules, which is the result of a non-adverse adaptive effect that is reversible once the sialotrophic agent has been eliminated. 23 This evidences a potential promotor effect in the synthesis of the biomolecules contained in these secretory granules. This could be answered under the dose response principle or the Arndt-Schultz principle, which states that low doses of low power infrared laser increase or decrease the physiological functions of a cell, and as the doses or stimuli increase, a plateau is reached where the beneficial physiological effect is suppressed, obtaining an adverse physiological response (Huang, Chen, Carroll, & Hamblin, 2009) (Ispizua, C. G., & Manzanedo, E. S. 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Unlike our findings, Sakamoto et al reported, without clinical signs for excessive salivation, enlargement and diffuse hypertrophy of acinar cells in the parotid gland accompanying ultrastructural changes in the animals fed with a diet containing 5% lac dye from a 13-week study ( Sakamoto et al, 1998 ; Fukumori et al, 2000 ) with additional involvement of submaxillary gland in the female group in the chronic study ( Sakamoto et al, 2000 ). These changes were considered as an adaptive nonadverse effect caused by unknown stimuli from the diet containing lac dye as also demonstrated in a rodent oral study on a grape skin extract-containing diet based on the reversal of parotid gland hypertrophy after cessation of administration ( Inoue et al, 2013 ; Inoue et al, 2014 ). Acidic solution is known to induce enlargement of salivary glands with salivation ( Cox et al, 1957 ) and the solution containing lac dye had low pH; pH 3.82 for 0.343 mg/ml ( Kongkachuichay et al, 2002 ) and pH 2.56 for 50 mg/ml in this study.…”
Section: Discussionmentioning
confidence: 94%